Formulaic sequences and perceived oral proficiency: putting a Lexical Approach to the test - Boers, Frank; Eyckmans, June; Kappel, Jenny; Stengers, Hélène; Demecheleer, Murielle (Language teaching research : LTR, 2006)
This study reports a small-scale experiment that was set up to estimate the extent to which (i) the use of formulaic sequences (standardized phrases such as collocations and idiomatic expressions) can help learners come across as proficient L2 speakers and (ii) an instructional method that emphasizes ‘noticing’of L2 formulaic sequences can help language learners add such phrases to their linguistic repertoire. Participants were 32 college students majoring in English. Over the course of 22 teaching hours they were exposed to considerable quantities of authentic listening and reading materials. During exploration of those materials, the experimental students (N = 17) were made aware of standardized word combinations, while in the control group (N = 15) the traditional grammar-lexis dichotomy was upheld. Afterwards, the participants’ oral proficiency was gauged in an interview by two blind judges. Both perceived the experimental group as more proficient than the control group. Two other blind judges counted the number of word combinations in the interviews that they considered to be formulaic sequences. Their counts correlated well with the oral proficiency ratings, which suggests that helping learners build a repertoire of formulaic sequences can be a useful contribution to improving their oral proficiency.